Practical support structures for selective laser melting - Gan, Ming Xuan (2018)
Support structure is an essential part in the selective laser melting process which are built especially in cases where reorientation does not eliminate overhanging features. These structures function as anchors, dissipate heat and prevent thermal warping of the parts. However, the materials used for the support structures are often discarded resulting in an increase in manufacturing time and costs. Therefore, this study explores three types of support structures to help design practical supports. As the levelness of each layer is critical in layered manufacturing process, experiments and finite element analysis were conducted to investigate the design effects on manufacturing thin plates and cuboids. The results revealed that the orientation and distribution of the support structures influence the levelness of the built part. Uniformly spaced vertical struts, of only 2.2% overhang-support contact area, enables fabrication of relatively levelled thin plates. Finite element analysis also showed that unequally spaced support structures changes the heat dissipation pattern in the thin plate which can lead to thermal distortions. The results also indicated that the angle between the support structures and the shrinkage direction of more than 90 ° prevents upward thermal warpages.